China Rising in Historical Perspective - Doyle, G. Wright (Journal of Research for Christianity in China (JRCC), 2025)
We are standing at a pivotal moment in human history. Over the course of the past few thousand years, countless kings and countries have gained ascendancy over their neighbors for a while, only to be replaced at the pinnacle of influence by an upstart rival. Only rarely, however, do entire civilizations either gain or lose a position of dominance. That sort of transition – which really deserves to be called a revolution – is taking place before our very eyes. Such colossal shifts in power and prestige are fraught with danger, but also filled with exciting possibilities. In this article we shall ponder the rise of China in the context of history, in order to reflect upon our possible responses and roles in this tectonic geo-political shift. Moving quickly over continents and centuries, I shall make five observations about rising China, and conclude with some suggestions for both Western and Chinese Christians.